A study on consumer acceptance of fish sausage (empek-empek) leptobarbus hoevenii added with Carrots (daucus carota) - Sri Tika Evianty S; N. Ira Sari; Sumarto ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
The study was conducted to determine consumer acceptance of fish sausage added with carrots. About 6 kg river carp was taken from a fish market in Pekanbaru. Four groups of fish sausage were prepared from river carp meat and tapioca flour; and each of them was fortified with 0%, 10%, 20% and 30% of carrots to improve their colour. The fish sausage were evaluated for consumer acceptance; moisture, protein, ash, and crude fiber. The results indicated that the fish sausage added with 20% carrots was the most preferable by consumers. The river carp sausage contained: 48,96% moisture, 21,59% protein, 1,86% ash and 7,12% crude fiber.Keyword: Fish sausage, River carp, carrots, consumer acceptance.